2005
DOI: 10.1211/jpp.57.10.0014
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive action of the extract and the flavonoid quercitrin isolated from Bauhinia microstachya leaves

Abstract: This study examined the antinociceptive effect of Bauhinia microstachya (Leguminosae), a native plant widely distributed in the South of Brazil, in several chemical and mechanical models of pain. The methanolic extract (ME) from B. microstachya (3--30 mg kg(-1), i.p.) and the isolated compound quercitrin (1--10 mg kg(-1), i.p.), given 30 min earlier, produced a dose-dependent inhibition of acetic-acid-induced visceral pain in mice, with a mean ID50 value (dose necessary to reduce the nociceptive response by 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 27 publications
0
30
0
3
Order By: Relevance
“…It is noteworthy in this aspect that quercitrin has been reported to be present in khoyer (Rajendra et al, 2011). Antinociceptive activity as demonstrated by inhibition of acetic acid-induced visceral pain in mice has been reported for Bauhinia microstachya leaf extract as well as the isolated active component from leaf, quercitrin (Gadotti et al, 2005). Quercitrin also reportedly demonstrated significant anti-inflammatory activity against 12-Otetradecanoyl-13-acetate-induced mouse ear edema (Erdemoglu et al, 2008).…”
Section: Resultsmentioning
confidence: 95%
“…It is noteworthy in this aspect that quercitrin has been reported to be present in khoyer (Rajendra et al, 2011). Antinociceptive activity as demonstrated by inhibition of acetic acid-induced visceral pain in mice has been reported for Bauhinia microstachya leaf extract as well as the isolated active component from leaf, quercitrin (Gadotti et al, 2005). Quercitrin also reportedly demonstrated significant anti-inflammatory activity against 12-Otetradecanoyl-13-acetate-induced mouse ear edema (Erdemoglu et al, 2008).…”
Section: Resultsmentioning
confidence: 95%
“…Quercitrin Quercitrin (quercetin 3-O-alpha-L-rhamnopyranoside) (Figure 1) is a flavone glycoside and has anti-leishmanial, anti-nociceptive and anti-inflammatory activity (Camuesco et al 2004;Gadotti et al 2005;Muzitano et al 2006). It has demonstrated a potent anti-leishmanial activity (IC 50 approximately 1 mg mL −1 ) with a low toxicity profile (Muzitano et al 2006).…”
Section: Flavonoidsmentioning
confidence: 99%
“…Since previous studies have shown that the flavonoids quercetin, quercitrin and hyperoside possess antinociceptive effects when tested individually [33][34][35], it is possible that the flavonoids present in the methanol extracts and butanol fraction of this species may be responsible, at least in part, for the antinociceptive effects reported here. On the other hand, since the benzophenone derivatives were detected as major compounds in the chloroform fraction and their subfractions, it can be hypothesized that these compounds may be also associated with the effects found in the present study.…”
Section: Discussionmentioning
confidence: 80%